2011
DOI: 10.1113/jphysiol.2011.211052
|View full text |Cite
|
Sign up to set email alerts
|

Changes of SERCA activity have only modest effects on sarcoplasmic reticulum Ca2+ content in rat ventricular myocytes

Abstract: Changes of the activity of the sarco-endoplasmic reticulum Ca(2+)-ATPase (SERCA) affect the amplitude of the systolic Ca(2+) transient and thence cardiac contractility. This is thought to be due to alterations of SR Ca(2+) content. Recent work on mice in which the expression of SERCA is decreased found that a large reduction of SERCA expression resulted in a proportionately much smaller decrease of SR Ca(2+) content. The aim of the current work was to investigate the quantitative nature of the dependence of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 29 publications
2
34
0
1
Order By: Relevance
“…Figure 3A shows the effects of the SERCA inhibitor, thapsigargin, on both stimulated Ca transients and caffeine responses. The experiments were performed in ISO (100 nM); thapsigargin (5 µM) was applied for 90 s. In agreement with previous work, 27–29 and as shown by the normalized traces of Figure 3C , thapsigargin slowed the decay of the systolic Ca transient. This was associated with a fall in SR Ca content as shown by the decrease in both the caffeine-evoked increase of Ca and the integral of the accompanying NCX current ( Figure 3B ).…”
Section: Resultssupporting
confidence: 88%
“…Figure 3A shows the effects of the SERCA inhibitor, thapsigargin, on both stimulated Ca transients and caffeine responses. The experiments were performed in ISO (100 nM); thapsigargin (5 µM) was applied for 90 s. In agreement with previous work, 27–29 and as shown by the normalized traces of Figure 3C , thapsigargin slowed the decay of the systolic Ca transient. This was associated with a fall in SR Ca content as shown by the decrease in both the caffeine-evoked increase of Ca and the integral of the accompanying NCX current ( Figure 3B ).…”
Section: Resultssupporting
confidence: 88%
“…Many published studies have shown that strong inhibition of I to can increase CaTA [3, 39, 4749] and inhibition of SERCA can decrease it [50, 51]. Some studies have also further shown that I to inhibition can have greater effects in epicardial cells [3, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Bode et al . [51] demonstrated that when voltage-clamped rat CMs were excited with 100 ms square depolarizing pulses, partial SERCA inhibition has a near-linear relationship with CaTA, a much stronger relationship than predicted by the Pandit model. However, in the absence of the endogenous AP waveform, it is impossible to draw conclusions about the relative importance of membrane currents and Ca 2+ handling proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, sarcolemmal efflux from the cell also contributes to this rate constant of decay. When the rate constant of decay of the caffeine-induced Ca 2+ transient (which includes sarcolemmal efflux but no SR uptake contribution) is subtracted from that of the electrically stimulated Ca 2+ transient (which includes the combined SR uptake and sarcolemmal efflux) 20 the % change in K SERCA induced by the supernatant was 114.3 ± 2.2% of media control. This compares well with the value (110.4 ± 1.2; Figure 2D iii) when using the rate decay constant of the electrically induced transient alone.…”
Section: Discussionmentioning
confidence: 99%